2021
DOI: 10.1177/09603271211002892
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal boron nitride nanoparticles trigger oxidative stress by modulating thiol/disulfide homeostasis

Abstract: Background: Hexagonal boron nitride nanoparticles (hBN NPs) are encouraging nanomaterials with unique chemical properties in medicine and biomedical fields. Until now, the optimal hBN NP’s dosage and biochemical mechanism that can be used for in vivo systems has not been fully revealed. The main aim of this article is to reveal characteristics, serum and tissue interactions and any acute cytotoxic effect of different dose of hBN NPs for the first time. Methods: hBN NPs at concentrations varying between 50–3200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In Wistar albino rats, it has been determined that hBNNPs increased oxidative stress. In the cardiac tissues, 3200 μg/kg dose of hBNNPs caused a statistically more significant increase in LOOH levels than the controls [37].…”
Section: Cardiovascular Systemmentioning
confidence: 81%
“…In Wistar albino rats, it has been determined that hBNNPs increased oxidative stress. In the cardiac tissues, 3200 μg/kg dose of hBNNPs caused a statistically more significant increase in LOOH levels than the controls [37].…”
Section: Cardiovascular Systemmentioning
confidence: 81%
“…Apart from GBMs, other 2D materials such as hBN and TMDs have been investigated in the liver, pancreas, and spleen. In another study, the acute (24 h) impact of hBN (in the range of 50–200 nm) after intravenous administration at 0.5–3.2 mg/kg was investigated in Wistar rats . Effects were identified at the two highest doses on thiol–disulfide homeostasis in serum (measuring total thiol, native thiol, and disulfide concentrations).…”
Section: Impact On Liver Spleen and Kidneysmentioning
confidence: 99%
“…Further investigating the thiol–disulfide homeostasis in different organs, (e.g., liver, spleen, kidney, heart, and pancreas), changes to homeostasis were found in the heart and spleen at 0.8 mg/kg but not at higher doses. In addition, the authors reported an increase in the level of lipid hydroperoxides (proxy for oxidative stress) and myeloperoxidase (proxy for neutrophil infiltration and inflammation) and a decrease in catalase levels (proxy for antioxidant defense) at the two highest doses in the same organs . The main limitation of the above study is that a single time point was analyzed, leaving open the question of long-term impact of such alterations or possible recovery/resolution.…”
Section: Impact On Liver Spleen and Kidneysmentioning
confidence: 99%
“…According to literature, only the edges of hBN can become chemically active, and only the electrophilic boron atoms of these edges can form covalent bonds with OHradicals. 70,71 At the same time, the in-plane bonds of hBN are very strong, which means that hBN sheets in few-layers flakes are less prone to breakage during the exfoliation, and fewer edges are created. 72,73 As for the transition-metal dichalcogenides, there are several references about their gas barrier properties, antibacterial and thermal resistance ability.…”
Section: Gnps Boost Further Multi-functionalities Into Paintsmentioning
confidence: 99%